AN ANALYSIS OF IDIOMATIC EXPRESSION FOUND IN NIKI’S SELECTED SONG LYRICS - Putri Alicya (Journal of English Education and Literature, 2025)
This research aims to identify and analyze the types and meanings of idiomatic found in three selected songs by NIKI from the album Live at The Wiltern, namely Lose, Lowkey, and Backburner. The focus of this research is to investigate how idiomatic expressions contribute to the overall meaning and emotional depth of the lyrics. The researcher uses a qualitative descriptive method and applies the theory proposed by Boatner and Gates to classify the types of idioms. The data were collected by listening to the songs, transcribing the lyrics, identifying idiomatic expressions, and analyzing their meanings based on context. The findings show that a total of 24 idiomatic expressions were identified in the three songs. These idioms consist of various types, including lexemic idiom noun, verb, adjective, adverbial, and phrasal idioms. Each idiom contributes to the thematic richness of the lyrics, expressing feelings of love, heartbreak, self-reflection, and personal growth. The use of idioms in the lyrics adds depth and emotional nuance, making the songs more expressive and relatable for listeners. This research is expected to provide insights for English learners, teachers, and future researchers about the importance of idiomatic expressions in song lyrics as a tool for enhancing language comprehension and cultural understanding.